(untitled) (Universal International Scientific Journal, 2026)
This scientific article analyzes modern methods of applying scientific research in history, in particular, the role of digital history, GIS technologies and 3D modeling. The study covers the issues of preserving and promoting historical heritage by synthesizing traditional methodology with innovative approaches. The purpose of the study is to assess the effectiveness of integrating scientific developments in history into education, museum work and political decision-making processes, and practical recommendations are developed using the example of the history of Uzbekistan.